Quantitative or Qualitative Forward Guidance: Does it Matter? - Gunda-Alexandra Detmers; Özer Karagedikli; Richhild Moessner (Center for Economic Studies and ifo Institute (CESifo), 2018)
Every monetary policy decision by the Reserve Bank of New Zealand (RBNZ) is accompanied by a written statement about the state of the economy and the policy outlook, but only every second decision by a published interest rate forecast. We exploit this difference to study the relative influences of qualitative and quantitative forward guidance. We find that announcements that include an interest rate forecast lead to very similar market reactions across the yield curve as announcements that only include written statements. We interpret our results as implying that central bank communication is important, but that the exact form of that communication is less critical. Our results are also consistent with market participants understanding the conditional nature of the RBNZ interest rate forecasts.
Keywords: E43; E44; E52; E58; G12; 330; monetary policy; forward guidance; interest rate forecasts